2014
DOI: 10.4236/health.2014.610128
|View full text |Cite
|
Sign up to set email alerts
|

Concerns about One’s Own Future or Securing Child’s Future: Paradox of Childbearing Decision Making

Abstract: Background and Purpose: Researchers' incomplete perception of the concerns about childbearing decision making process is revealed in discussions about policies and programs that are designed to influence fertility. Perceiving the concerns of women is essential to explain process of decision making for childbearing. This study aimed to understand women's main concerns about childbearing decision making. Methods: This qualitative study was performed by conventional content analysis approach. The participants inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Religious beliefs and rules about contraceptive use, abortions, gender roles and the importance of the family are associated with fertility rates [120,121]. Greater religiosity and religious activity are associated with higher fertility [122][123][124][125].…”
Section: (N) Religiositymentioning
confidence: 99%
See 1 more Smart Citation
“…Religious beliefs and rules about contraceptive use, abortions, gender roles and the importance of the family are associated with fertility rates [120,121]. Greater religiosity and religious activity are associated with higher fertility [122][123][124][125].…”
Section: (N) Religiositymentioning
confidence: 99%
“…Attitudes toward reproduction in wealthy families became less favourable as parity increased, suggesting that the direct cost of children is a salient theme in fertility decision-making. Kariman et al [120] also found that, among Iranian women, financial security, and securing their own and their children's futures, were primary concerns of childbearing. In Portuguese men and women, economic concerns were also a salient issue [71].…”
Section: (L) Cost Of Childrenmentioning
confidence: 99%
“…Many studies have examined the changes in fertility rates and in the factors influencing fertility in Iran and other countries (Testa et al, 2012;Kohan et al, 2012). The results of these studies show the direct relationship of fertility with women's age (Kariman et al, 2014b;Daniluk & Koert, 2012;Brennan et al, 2011;Mills et al, 2011), marital age (Hosseinzadeh et al, 2010;Kariman et al, 2014b;Taghizadeh et al, 2015), sexual preferences (Akaberi et al, 2008;Mills et al, 2011;Bhat & Zavier, 2003;Adibi Sedeh et al, 2012), desired number of children (Kariman et al, 2014a;Akaberi et al, 2008;Testa et al, 2012;Kohan et al, 2012;Daniluk & Koert, 2012;Brennan et al, 2011;Mills et al, 2011;Bhat & Zavier, 2003;Sedeh et al, 2012;Tavares, 2010) and child mortality (Sadeghi et al, 2010) and its indirect relationship with marital age (Sedeh et al, 2012) and couples' level of education (Tavares, 2010;Sadeghi et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…A long-term process of reflection and intellectual debate may therefore precede childbearing. Previous studies on fertility have failed to take into account the process of childbearing decision-making (Rijken & Knijn, 2009;Kariman et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Some factors such as proper higher education, availability of the proper health network system in remote areas, economic strength, staying in education longer, delaying marriage are likely to have an indirect effect on fertility rate declination. Today, the sociologists of Iran are getting more concerned about the future of the country's population (Kariman 2014). Keeping in mind about the reduced rate of population, in the year 2012, the government of Iran started an incentive policy as per which, Housekeeping has been considered as a career and in which provision of pension also allocated.…”
Section: Abstract Introductionmentioning
confidence: 99%